Intellectual property and public health in the developing world - Azam, Mohammad Monirul (Open Book Publishers, 2016)
"Across the world, developing countries are attempting to balance the international standards of intellectual property concerning pharmaceutical patents against the urgent need for accessible and affordable medicines. In this timely and necessary book, Monirul Azam examines the attempts of several developing countries to walk this fine line. He evaluates the experiences of Brazil, China, India, and South Africa for lessons to guide Bangladesh and developing nations everywhere. Azam's legal expertise, concern for public welfare, and compelling grasp of principal case studies make Intellectual Property and Public Health in the Developing World a definitive work. The developing world is striving to meet the requirements of the World Trade Organization's TRIPS Agreement on intellectual property. This book sets out with lucidity and insight the background of the TRIPS Agreement and its implications for pharmaceutical patents, the consequences for developing countries, and the efforts of certain representative nations to comply with international stipulations while still maintaining local industry and public health. Azam then brings the weight of this research to bear on the particular case of Bangladesh, offering a number of specific policy recommendations for the Bangladeshi government--and for governments the world over. Intellectual Property and Public Health in the Developing World is a must-read for public policy-makers, academics and students, non-governmental organizations, and readers everywhere who are interested in making sure that developing nations meet the health care needs of their people."--Publisher's website